Conflict of interest and signal interference lead to the breakdown of honest signalling - Popat, Roman; Pollitt, Eric J.G.; Harrison, Freya; Naghra, Hardeep; Hong, Kar Wei; Chan, Kok Gan; Griffin, Ashleigh; Williams, Paul; Brown, Sam P.; West, Stuart A.; Diggle, Stephen P. (Wiley, 2015)
Animals use signals to coordinate a wide range of behaviours, from feeding offspring to predator avoidance. This poses an evolutionary problem, because individuals could potentially signal dishonestly to coerce others into behaving in ways that benefit the signaller. Theory suggests that honest signalling is favoured when individuals share a common interest and signals carry reliable information. Here, we exploit the opportunities offered by bacterial signalling, to test these predictions with an experimental evolution approach. We show that: (1) a reduced relatedness leads to the relative breakdown of signalling; (2) signalling breaks down by the invasion of mutants that show both reduced signalling and reduced response to signal; (3) the genetic route to signalling breakdown is variable; (4) the addition of artificial signal, to interfere with signal information, also leads to reduced signalling. Our results provide clear support for signalling theory, but we did not find evidence for the previously predicted coercion at intermediate relatedness, suggesting that mechanistic details can alter the qualitative nature of specific predictions. Furthermore, populations evolved under low relatedness caused less mortality to insect hosts, showing how signal evolution in bacterial pathogens can drive the evolution of virulence in the opposite direction to that often predicted by theory.